The excited-state dynamics of the radical anions of cyanoanthracenes. Issue 1 (14th December 2021) - Beckwith, Joseph S.; Aster, Alexander; Vauthey, Eric
Abstract : The excited-state lifetime of the radical anion of cyanoanthracenes in liquids is at least three orders of magnitude shorter than previously deduced from indirect measurements. This limits their application in photoredox catalysis. Abstract : The radical anion of 9, 10-dicyanoanthracene (DCA ) has been suggested to be a promising chromophore for photoredox chemistry, due to its nanosecond excited-state lifetime determined from indirect measurements. Here, we investigate the excited-state dynamics of the radical anion of three cyanoanthracenes, including DCA˙ −, produced by photoinduced electron transfer in liquid using both pump–probe and pump–pump probe transient electronic absorption spectroscopy. All three excited radical ions are characterised by a 3–5 ps lifetime, due to efficient non-radiative deactivation to the ground state. The decay pathway most probably involves D1 /D0 conical intersection(s), whose presence is favoured by the enhanced flexibility of the radical anions relative to their neutral counterparts. The origin of the discrepancy with the nanosecond lifetime of DCA˙ − * reported previously is discussed. These very short lifetimes limit, but do not preclude, photochemical applications of the cyanoanthracene anions.